Breaking the bonds : marital discord in Pennsylvania, 1730-1830 - Smith, Merril D., 1956- (American social experience series, 1991)
""In Breaking The Bonds, Merril Smith establishes the ambitious goal of determining 'what kind of problems arose in troubled marriages' and of analyzing 'how men and women coped with marital discord.' ... To accomplish this, Smith studied hundreds of divorce petitions, other legal documents, newspapers, almshouse dockets, and prescriptive literature. She concludes that, as in the present day, married couples fought and parted over sex, money, and abuse.""--Pennsylvania History. ""A richly textured study. . . With an eye to cross-class and cross-race representation, Smith utilizes diverse